Events management - Bowdin, G. A. J. (Events management, 2023)
"A must-have introductory text of unrivalled coverage and depth focusing on events planning and management, the fourth edition of Events Management provides a complete A to Z of the principles and practices of planning, managing and staging events. This book has been dubbed 'the events management bible' and fosters an interactive learning experience amongst scholars of events management, tourism and hospitality"--